Globalization and Self-Organization in the Knowledge-Based Society - Christian Fuchs (tripleC: Communication, Capitalism & Critique)
In this paper I suggest that a theory of self-organization can be used as a consistent background theory for explaining the dynamics and logics of globalization. Globalization is not confined to the human realm, it is an attribute of all complex, self-organizing systems. Globalization in a synchronous sense means a micro-macro-link where bottom-up-emergence of new qualities in the self-reproduction of complex systems takes place, it is accompanied by a macro-micro-link of top-down-localization. A dynamic interaction between a global and a local level (glocalization) results in the permanent overall self-reproduction of the system. Globalization in a diachronic sense means the emergence of a new, higher level of self-organization during a phase of instability and heavy fluctuations by order through fluctuation. Globalization is shaped by a dialectic of change and continuity: in the hierarchy that stems from emergent evolution there are both general aspects of globalization and aspects that are specific for each organizational level. Applying this general notion of globalization to society means that human globalization is both a general process that can be found in all societies and a specific process with emergent qualities in concrete phases of societal development. Globalization processes in modern society are based on structural antagonisms that result in uneven developments in the technosphere, the ecosphere, the economy, polity, and culture. The transition to Postfordist, informational capitalism has been a consequence of the development of the structural antagonisms of Fordism and has been accompanied by a new phase of globalization that has transformed the subsystems of society and has resulted in new antagonism that are an expression of general antagonisms that shape modern societies. Hence we find antagonistic tendencies of contemporary globalization in all subsystems of society that result in both risks and opportunities. Human beings have the ability to actively shape society in such a way that an alternative sustainable form of globalization can be achieved.